Rebuilding the Christian Commonwealth New England congregationalists and foreign missions, 1800-1830 - Andrew, John A. (Lexington : The University Press of Kentucky, 2015)
The foreign missionary movement of the early 19th century grew out of the efforts of churches in New England to deal with the changes then taking place in society. The erosion of traditional institutional structures and social values plus the rise of Unitarianism threatened the destruction of the traditional faith. Mr. Andrew holds that the Congregational clergy used foreign missions not only to implant New England culture in heathen lands but also to awaken a sense of community at home.
Cover; Half-title; Title; Copyright; Contents; Acknowledgments; Introduction; 1. The Search for Identity; 2. A Panorama of Change; 3. The New England Clergy and the Problem of Permanency; 4. The Glory Is Departed; 5. Enlisting the Public; 6. The System at Work: The Sandwich Islands Mission; 7. The Struggle for Stability; 8. Achieving Permanence; 9. Fighting the Way to Empire; Appendix: A Note on Sources; Notes; Bibliographical Essay; Index.
Print version record.
Keywords: American Board of Commissioners for Foreign Missions; Congregational churches -- Missions; Congregational churches -- New England -- History; New England -- Church history; RELIGION -- Christian Ministry -- Missions; RELIGION / Christian Ministry / Missions; Electronic books